Peel-off emulgel mask of Cocos nucifera L. Extract using gelling agent carbomer 940 as antiacne against Propionibacterium acnes ATCC 11827 - Dewi Melani Hariyadi; Isnaeni Isnaeni; Sisunandar Sudarma; Suciati Suciati; Noorma Rosita (Journal of Advanced Pharmaceutical Technology & Research, 2020)
Cocos nucifera Linn., which contain lauric acid has been known had antibacterial activity against Propionibacterium acnes that usually improve severe of pimple. Current study investigated optimum formula of emulgel mask based on the C. nucifera L. Extract from Kopyor coconut. Extract were tested for antibacterial against P. acnes ATCC 11827. In this research, C. nucifera L. extract of 1 and 5% were formulated as an active agent of peel off antiacne emulgel mask-containing carbomer 940 in various concentration (1% and 1.5%). The peel-off emulgel mask of C. nucifera L extract was then evaluated in terms of viscosity, pH, drying time, spreadability, and antibacterial activity. The selected formula was formula containing 5% of extract and 1% of carbomer 940. This formula had pH that suitable with skin pH 4.5–6.5, had good spreadability, and also produced highest antibacterial activity against P. acnes.